Organisation trophique de la malacofaune benthique non cultivée du bassin ostréicole de Marennes-Oléron - Sauriau, Pierre-guy; Mouret, Véronique; Rince, Jean-philippe (Gauthier-Villars, 1989)
Stock assessment of wild soft-bottom molluscs formed part of a study carried out in the Marennes-Oléron oyster-farming bay. The sampling design was based on a stratified random sampling. The results are presented using three descriptors: species richness, abundance and biomass. In spring 1984, wild molluscs corresponded to nearly 20% of oyster-rearing stocks. Knowledge of the feeding behaviour and geographical distribution of the various trophic groups within the bay enables to estimate trophic competition with the cultivated species (Crassostrea gigas and Mytilus edulis). Five trophic groups were specified: suspension-feeders, deposit-feeders, suspension/deposit feeders, carnivores and herbivores. Their organization in terms of species number seemed to be homogeneous throughout the bay, with the exception of the Charente and Seudre estuaries. In these areas, the trophic system was conspicuously reduced: the dominance of mixed groups composed of suspension/deposit-feeder increased. Geographically, suspension-feeders were more numerous in the sublittoral areas and also in the sandy tidal flats. The biomass of these suspension-feeders (e. g Cerastoderma edule, . MYliIus edulis, Crepiduia fornicata and Solen marginatus) corresponded to 75% of the wild mollusc stock. In contrast, the deposit-feeding Hydrobia ulvae and Abra tenuis were more numerous on all mud flats, as were the suspension/deposit-feeding Macoma balthica and Scrobicularia plana. The close concordance between this trophic system and its local geographical variations, on the one hand and the hydrological typology of the bay on the other, indicated that water turbidity appears to be the main factor structuring this ecosystem, with sediment type exercising a secondary influence. The presence of oyster-farming cultures will also affect the molluscan trophc system by encouraging those deposit-feeders or suspension/deposit-feeders. In the case of suspension-feeding molluscs, it was necessary to integrate physiological capacities, i. e filtration rate and ...